2020
DOI: 10.1002/cncr.32898
|View full text |Cite
|
Sign up to set email alerts
|

Congruence of patient‐ and clinician‐reported toxicity in women receiving chemotherapy for early breast cancer

Abstract: Background The National Cancer Institute's Patient‐Reported Outcomes Version of the Common Terminology Criteria for Adverse Events, collected alongside the clinician‐reported Common Terminology Criteria for Adverse Events, enables comparisons of patient and clinician reports on treatment toxicity. Methods In a multisite study of women receiving chemotherapy for early‐stage breast cancer, symptom reports were collected on the same day from patients and their clinicians for 17 symptoms; their data were not share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 41 publications
2
15
1
2
Order By: Relevance
“…Overall, we found fair agreement for long-lasting symptoms, whereas for the more recent symptoms (defined as those recorded 1-7 days earlier), the degree of agreement in symptom reporting between the patient and physician was moderate and comparable to results from a study in early breast cancer [ 19 ]. However, the congruence between patients and physicians gained substantial reliability when analyses on levels of agreement in subgroups of the specific symptoms (ie, pain, fever, diarrhea, obstipation, nausea, vomiting, and stomatitis) were performed and also in an identical manner to that in the most frequently occurring symptoms, including fatigue, hot flashes, sleep disorder, headache, and taste disorder.…”
Section: Discussionsupporting
confidence: 74%
“…Overall, we found fair agreement for long-lasting symptoms, whereas for the more recent symptoms (defined as those recorded 1-7 days earlier), the degree of agreement in symptom reporting between the patient and physician was moderate and comparable to results from a study in early breast cancer [ 19 ]. However, the congruence between patients and physicians gained substantial reliability when analyses on levels of agreement in subgroups of the specific symptoms (ie, pain, fever, diarrhea, obstipation, nausea, vomiting, and stomatitis) were performed and also in an identical manner to that in the most frequently occurring symptoms, including fatigue, hot flashes, sleep disorder, headache, and taste disorder.…”
Section: Discussionsupporting
confidence: 74%
“…Although the women in the current study scored symptom interference as consistently lower than symptom severity, the high prevalence of moderate or higher symptom severity in both age groups underscores the importance of ongoing symptom monitoring in patients of all ages and communication regarding symptom management with the treatment team 30,31 . It is perhaps easier for patients to communicate that a symptom is interfering with their daily activities rather than convey the absolute severity of a symptom, which may explain why clinicians are reported to often underestimate actual symptom intensity 18 …”
Section: Discussionmentioning
confidence: 69%
“…We previously observed that patient‐reported symptom severity varies significantly among 4 chemotherapy regimens commonly used in current clinical practice for the treatment of early breast cancer, and that patients receiving anthracycline‐based regimens had significantly higher rates of moderate, severe, or very severe (MSVS) symptoms compared with patients receiving regimens that were not anthracycline based 17 . In this sample of patients, we also observed that clinicians often underestimate the severity of chemotherapy side effects compared with patient reports of symptom severity 18 …”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Recently, Patient-Reported Outcomes Version of the Common Terminology Criteria for Adverse Events (PRO-CTCAE) has been developed as a novel, validated, and reliable method for reporting patient-reported adverse events [14][15][16][17]. Because investigator-reported CTCAE (IR-CTCAE) often under-detects symptomatic adverse events, PRO-CTCAE can be used to enhance the precision and patientcenteredness of adverse event reporting in cancer clinical research [18,19]. In this study, we report acute PRO-CTCAE of proton beam therapy for patients with high or unfavorable-intermediate risk prostate cancer who received radiotherapy to the prostate/seminal vesicles and the regional pelvic lymph nodes in a prospective clinical trial.…”
Section: Introductionmentioning
confidence: 99%